Using prognosis to guide inclusion criteria, define standardised endpoints and stratify follow‐up in active surveillance for prostate cancer. (2nd June 2019) - Gnanapragasam, Vincent J.; Barrett, Tristan; Thankapannair, Vineetha; Thurtle, David; Rubio‐Briones, Jose; Domínguez‐Escrig, Jose; Bratt, Ola; Statin, Par; Muir, Kenneth; Lophatananon, Artitaya
Abstract : Objectives: To test whether using disease prognosis can inform a rational approach to active surveillance (AS) for early prostate cancer. Patients and methods: We previously developed the Cambridge Prognostics Groups (CPG) classification, a five‐tiered model that uses prostate‐specific antigen (PSA), Grade Group and Stage to predict cancer survival outcomes. We applied the CPG model to a UK and a Swedish prostate cancer cohort to test differences in prostate cancer mortality (PCM) in men managed conservatively or by upfront treatment in CPG2 and 3 (which subdivides the intermediate‐risk classification) vs CPG1 (low‐risk). We then applied the CPG model to a contemporary UK AS cohort, which was optimally characterised at baseline for disease burden, to identify predictors of true prognostic progression. Results were re‐tested in an external AS cohort from Spain. Results: In a UK cohort ( n = 3659) the 10‐year PCM was 2.3% in CPG1, 1.5%/3.5% in treated/untreated CPG2, and 1.9%/8.6% in treated/untreated CPG3. In the Swedish cohort ( n = 27 942) the10‐year PCM was 1.0% in CPG1, 2.2%/2.7% in treated/untreated CPG2, and 6.1%/12.5% in treated/untreated CPG3. We then tested using progression to CPG3 as a hard endpoint in a modern AS cohort ( n = 133). During follow‐up (median 3.5 years) only 6% (eight of 133) progressed to CPG3. Predictors of progression were a PSA density ≥0.15 ng/mL/mL and CPG2 at diagnosis. Progression occurred in 1%, 8% and 21% of men with neither factor, only one, or both, respectively. In an independent Spanish AS cohort ( n = 143) the corresponding rates were 3%, 10% and 14%, respectively. Conclusion: Using disease prognosis allows a rational approach to inclusion criteria, discontinuation triggers and risk‐stratified management in AS.